Educational Technology for Developing Health and Environmental Competencies in Teaching “Man and Nature” 5th -6th Grade - Stanislava Yordanova; Antoaneta Angelacheva (Педагогически форум)
The article presents an invariant of a didactic technology for forming a system of knowledge, skills, and value-based attitudes among students towards the environment and human health. The effectiveness of any educational technology depends on the selected set of "tools"—approaches, organizational forms, methods, teaching tools, and the interconnections between them. Therefore, this study justifies the selection of technology components that ensure its functioning in the teaching of “Man and Nature” in the 5th and 6th grades, with a focus on health and environmental education. The feasibility of the modeled technology has been confirmed through a pedagogical experiment. In every instance of its application, the technology enables the simultaneous development of both invariance and variability, granting it the qualities of a relatively stable yet dynamic and open system.